2007
DOI: 10.5459/bnzsee.40.2.69-77
|View full text |Cite
|
Sign up to set email alerts
|

Proposed macro-model for the analysis of infilled frame structures

Abstract: Reinforced concrete frames infilled with masonry panels constitute an important part of the high-risk structures in different regions of high seismicity. In some developing countries, they are still used as main structural system for low to medium rise buildings. Consequently, reliable methods to analyse infilled frames are required in order to reduce the loss of life and property associated with a possible structural failure. The equivalent strut model, proposed in the 1960s, is a simple procedure to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(97 citation statements)
references
References 5 publications
2
87
1
7
Order By: Relevance
“…Three different types of strut model have been proposed to simulate the behaviour of infilled frames: single strut, double strut, and triple strut [24,25]. Experiments on masonry infill panels have also revealed that the equivalent strut must have a representative width in order to accurately represent the infill.…”
Section: Introductionmentioning
confidence: 99%
“…Three different types of strut model have been proposed to simulate the behaviour of infilled frames: single strut, double strut, and triple strut [24,25]. Experiments on masonry infill panels have also revealed that the equivalent strut must have a representative width in order to accurately represent the infill.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Crisafulli and Carr [152] proposed an improved strut model to compute the behaviour of infilled frame systems. For that, it was presented an integration of struts and spring to computing independently two phenomena: (i) diagonal cracking and corner crushing and (ii) shear sliding.…”
Section: Advances In Civil Engineeringmentioning
confidence: 99%
“…A number of researchers (Chrysostomou et el. [7], [8], Crisafulli [9] El-Dakhkhni et al [10], [11], [12], Crisafulli and Carr [13], Rodrigues et al [14], [15], Mihaleva [6] et al) modified firstly proposed single diagonal using few diagonals gathered in one model. As a result of this the contact zones and interface surfaces are more precisely modelled especially opening the tensile surfaces located at the edge.…”
Section: Equivalent Diagonal Compression Strutmentioning
confidence: 99%